Analisis Kadar Flavonoid Total dan Aktivitas Antioksidan dari Ekstrak Etanol Serta Fraksi dari Gagang Cengkeh (Syzygium Aromaticum (L)). - Intan Oktaviana Putri; Niken Luthfiyanti; Danang Raharjo (Universitas Muhammadiyah Manado, 2025)
Antioxidants are substances that can inhibit oxidation caused by free radicals. Flavonoids are effective natural antioxidants due to their unique chemical structure. Both have a hydroxyl group (-OH) attached to an aromatic ring. This hydroxyl group can donate hydrogen or electrons to free radicals. Clove stems (Syzygium aromaticum (L.)) are known to possess bioactive compounds, including flavonoids like quercetin and kaempferol, which act as antioxidants in protecting cells from free radicals. Maceration is a commonly used extraction method to obtain therapeutic compounds from plants. The process involves soaking the finely or coarsely ground plant material in a solvent (liquid thinner) in a closed container. Fractionation is a method for separating chemical components in an extract based on differences in their polarity or solubility. This process uses two immiscible solvents. This study is an experimental research aimed at determining the total flavonoid content (TFC) and the IC50​ value of the antioxidant activity present in the ethanol extract and fractions of clove stems (Syzygium aromaticum (L.)) using the ABTS method. The tests utilized maceration extraction with 96% ethanol as the solvent, and liquid-liquid fractionation using N-hexane, ethyl acetate, and water as solvents, along with UV-Vis spectrophotometry analysis. The results showed that the highest flavonoid content was in the ethanol extract, with a TFC value of 51.000 mgQE/g, and the highest antioxidant activity was in the ethyl acetate fraction, with an IC50​ value of 23.716 µg/mL, indicating a strong potential as a source of natural antioxidants.